Does the Culture of Hanging Out Affect Taxpayer Compliance In Paying Vehicle Tax - Tia, Maria Yoaneta; Helmi, Syarif M; Heniwati, Elok (Ilomata International Journal of Tax and Accounting, 2024)
There are motor vehicle tax arrears in Pontianak which are increasing every year so it is necessary to examine whether the consumptive factor hanging around taxpayers can influence taxpayer compliance. This research aims to explore the influence of a consumer lifestyle, especially in the context of hanging out activities, on taxpayer compliance in paying Motor Vehicle Tax (PKB) in Pontianak, West Borneo. The research method used in this research is descriptive quantitative. The data used is primary data using a questionnaire via Google Form. The population of this study were taxpayers who were registered and domiciled in Pontianak, West Kalimantan with a sample size of 191 people and used a simple random sampling method. This research data was tested using the SPSS version 29 software. The analytical method used are Linear Multiple Regression and Moderated Regression Analysis (MRA). The results show that the variables of hanging out and group hanging out behavior have a significant effect on compliance with paying PKB. However, the frequency of hanging out and spending on hanging out activities did not show a significant influence. Tax awareness does not significantly moderate the relationship between hanging out variables and tax compliance. The implication of this research is to encourage the implementation of an approach that is more focused on utilizing social norms and social interactions in community hangout culture to strengthen tax awareness and obligations, especially related to motor vehicle taxpayer compliance.